2015
DOI: 10.1186/s40942-015-0019-2
|View full text |Cite
|
Sign up to set email alerts
|

Triple combination therapy and zeaxanthin for the treatment of neovascular age-related macular degeneration: an interventional comparative study and cost-effectiveness analysis

Abstract: BackgroundReports of triple combination therapy for neovascular age-related macular degeneration (AMD) suggest a benefit, as do reports for zeaxanthin. An interventional comparative study was thus undertaken to evaluate the efficacy of triple combination therapy with and without zeaxanthin, as well as the economic viability of the therapies.MethodsThe cases of 543 consecutive eyes of 424 patients with subfoveal choroidal neovascularization (CNV) secondary to AMD were reviewed. All eyes were treated with triple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…This may be attributed, at least in part, to advanced stages of disease and by poor micronutrient absorption rates, which likely represents a limiting factor and should not be ruled out from clinical trials [ 122 , 326 ]. However, one preliminary report indicated that oral zeaxanthin supplementation, as an adjunct to an aggressive triple combination therapy regimen (including bevacizumab, steroid, and photodynamic therapy with verteporfin) for patients with subfoveal choroidal neovascularization, enhanced therapeutic efficiency and decreased the number of treatment cycles required [ 327 ]. Similar benefits were reported in cultured human RPE cells, following hypoxia-induced VEGF secretion, whereby treatment with zeaxanthin was suggested to offer direction protection against the pro-angiogenic factors contributing to neovascular lesions [ 328 ].…”
Section: Resultsmentioning
confidence: 99%
“…This may be attributed, at least in part, to advanced stages of disease and by poor micronutrient absorption rates, which likely represents a limiting factor and should not be ruled out from clinical trials [ 122 , 326 ]. However, one preliminary report indicated that oral zeaxanthin supplementation, as an adjunct to an aggressive triple combination therapy regimen (including bevacizumab, steroid, and photodynamic therapy with verteporfin) for patients with subfoveal choroidal neovascularization, enhanced therapeutic efficiency and decreased the number of treatment cycles required [ 327 ]. Similar benefits were reported in cultured human RPE cells, following hypoxia-induced VEGF secretion, whereby treatment with zeaxanthin was suggested to offer direction protection against the pro-angiogenic factors contributing to neovascular lesions [ 328 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent clinical study involving combinational therapy showed that zeaxanthin did protect the macula in already diseased eyes [ 43 ]. These studies in advanced AMD were different from AREDS2 in that they used 10-fold higher (and putatively more effective) doses of zeaxanthin (20 mg vs 2).…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with Z has been shown to improve visual performance and suppress retinal neovascularization that is characteristic of advanced AMD [38] while yielding a lower costutility ratio than identical treatments without Z supplementation [39]. The authors believe this paper provides the first evidence of resolution of a central dip in macular pigment density from dietary Z supplementation.…”
Section: Resultsmentioning
confidence: 57%